CXCL6 fuels the growth and metastases of esophageal squamous cell carcinoma cells both in vitro and in vivo through upregulation of PD‐L1 via activation of STAT3 pathway. Issue 7 (23rd December 2020) - Zheng, Shutao; Shen, Tongxue; Liu, Qing; Liu, Tao; Tuerxun, Aerziguli; Zhang, Qiqi; Yang, Lifei; Han, Xiujuan; Lu, Xiaomei
Abstract: CXCL6, contraction of C‐X‐C motif chemokine ligand 6, whose biological roles have been rarely described in esophageal squamous cell carcinoma (ESCC). To understand the clinicopathological and biological roles played by CXCL6 in the growth and metastasis of ESCC, immunohistochemistry was used to detect the expression of CXCL6 in ESCC tissues, totaling 105 cases; and the correlation was statistically analyzed between CXCL6 expression and clinicopathological parameters. The role mediated in migration and invasion was evaluated using wound‐healing and Transwell assays. MTT and flow cytometry were used to assay the proliferative variation. In vivo, tail vein injection model was established in nude mice xenografted with human ESCC cell lines whose CXCL6 were artificially manipulated. It was found that relative to normal control, CXCL6 was profoundly higher in ESCC; upregulated CXCL6 only significantly correlated with differentiation degree. In vitro, CXCL6 was found to promote the proliferation, migration, and invasion of ESCC cells; which was fully corroborated by nude mice experiment that CXCL6 can promote the growth and metastases of ESCC cells in vivo. Mechanistically, CXCL6 was discovered to be capable of promoting epithelial‐mesenchymal transition and upregulating PD‐L1 expression through activation of the STAT3 pathway. Collectively, all the data we showed here demonstrate that CXCL6 can enhance the growth and metastases of ESCC cells both in vivo and in vitro. Abstract : To the best of our knowledge, this is the first report describing the tumor‐promoting traits of CXCL6 in esophageal squamous cell carcinoma (ESCC) cells and the first study investigating the underlying mechanism by which CXCL6 promotes the immunoevasion of ESCC through upregulation of PD‐L1.